Sistim Pembangkit Biogas Model Portabel - Sonong Sonong; Muh Yusuf Yunus; Marhatang Marhatang; Remigius Tandioga; Herman Nauwir (Jurnal Teknik Mesin Sinergi, 2014)
Utilization of livestock manure has not been optimal, whereas livestock manure can be used as feedstock to produce renewable energy (renewable ) in the form of biogas . The problem that occurs is that people have not been able to utilize the manure waste especially cow dung as fuel alternative energy producers. Biogas is a mixture of combustible gas , which is produced by anaerobic fermentation of organic material such as animal manure and agricultural wastes in a digester chamber ( digester ) . In this study digester drum is made of plastic and stuffing materials derived from a mixture of cow dung and water . This study aims to design a portable device of biogas models are easy to assemble , inexpensive and can perform well . From the results of this study can be obtained biogas pressure and long flame generated by means of producing biogas and portable models can be applied to biogas stoves.